O trabalho do coordenador pedagógico com os professores iniciantes do Ensino Fundamental da Rede Municipal de Educação de Ponta Grossa/PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This dissertation has as study object, the pedagogical work from a pedagogical coordinator trough a critic viewpoint. The research problem that guides the scientific research is: How pedagogical coordinators develop their pedagogical work with teachers at their beginning career and how they observe their role on the process? The proposed main goal is to analyze the pedagogical work from pedagogical coordinator with beginner teachers at Municipal Schools from Ponta Grossa – Paraná. The specific goals are: Identify the pedagogical strategies from pedagogical coordinators at Municipal Schools from Ponta Grossa – Paraná, when working with beginner teachers; reveal the pedagogical coordinators perceptions about the starter teaching and their role on the process. It is related to a qualitative research (BOGDAN; BIKLEN, 1994), in this approach, collected data are mainly descriptive. For data analyzing, content analysis was used as methodological theoretical support (BARDIN, 2011). The acquired materials at the qualitative research has a lot of descriptions, circumstances, and happenings. The instruments from data collecting are a questionnaire with twenty coordinators and a semi-structured interview with five pedagogical coordinators active on the elementary teaching at Municipal Schools from Ponta Grossa. The research theoretical ground has mainly engaged with: André (2012), Bourdieu (1982, 1998, 2002, 2009), Brzezinski (2006), Gatti (2014), Huberman (1995), Marcelo Garcia (1992, 1999, 2009, 2010), Imbernón (2010), Papi e Martins (2019), Placco (2003, 2005, 2010, 2012, 2014), Romanowski (2010), Tardif (2010). The results show that, due to specific information lack to pedagogical coordinators from Municipal Education System (MES), which are related on working with beginner teachers, there is no consensus over the work from these professionals, but there is isolated strategies and service training to beginner teachers. Most of the participant coordinators notice the support needs to beginner teachers and their difficulties in the early career, they related these difficulties to two different points: faults in initial training and a natural process of learning from teaching. They mention positive aspects from arriving beginner teachers to the school environment. It is clear the intensification and bureaucratic work from pedagogic coordinators, what prevent the development of a better work.
Keywords: Coordenador pedagógico; Trabalho pedagógico; Professores iniciantes; Ensino Fundamental; Pedagogical coordinator; Pedagogical work; Beginner teachers; Elementary school; CNPQ::CIENCIAS HUMANAS::EDUCACAO